Evaluation of prospects for the development of e-commerce in Uzbekistan - Makhmudov Lazizbek Ubaydullo ugli (THE INNOVATION ECONOMY, 2026)
the article examines the prospects for e-commerce development in Uzbekistan. Using the innovative development model and PESTEL analysis, it explores political, economic, social, technological, environmental, and legal factors. Uzum Market illustrates innovative trends and consumer demands. Strategies involving AI and green logistics are proposed for further growth.